A novel approach to assess body composition in children with obesity from density of the fat-free mass. Issue 3 (March 2021) - Gutiérrez-Marín, Desirée; Escribano, Joaquin; Closa-Monasterolo, Ricardo; Ferré, Natalia; Venables, Michelle; Singh, Priya; Wells, Jonathan C.K.; Muñoz-Hernando, Judit; Zaragoza-Jordana, Marta; Gispert-Llauradó, Mariona; Rubio-Torrents, Carmen; Alcázar, Mireia; et al.
Summary: Background & aims: Assessment of Fat Mass (FM) and fat-free mass (FFM) using Air-displacement plethysmography (ADP) technique assumes constant density of FFM (DFFM ) by age and sex. It has been recently shown that DFFM further varies according to body mass index (BMI), meaning that ADP body composition assessments of children with obesity could be biased if DFFM is assumed to be constant. The aim of this study was to validate the use of the calculations of DFFM (rather than constant density of the FFM) to improve accuracy of body composition assessment in children with obesity. Methods: cross-sectional validation study in 66 children with obesity (aged 8–14 years) where ADP assessments of body composition assuming constant density (FFMBODPOD and FMBODPOD) were compared to those where DFFM was adjusted in relation to BMI (FFM adjusted and FM adjusted ), and both compared to the gold standard reference, the 4-component model (FFM4C and FM4C ). Results: FFMBODPOD was overestimated by 1.50 kg (95%CI -0.68 kg, 3.63 kg) while FFM adjusted was 0.71 kg (−1.08 kg, 2.51 kg) (percentage differences compared to FFM4C were 4.9% (±2.9%) and 2.8% (±2.1%), respectively ( p  < 0.001)). Consistently, FM was underestimated by both methods, representing a mean difference between methods of 4.0% (±2.9%) and 6.8% (±3.8%), respectively, when compared to the reference method. The agreement and reliability of body composition assessments were improved when adjusted using calculations (adjusted models) rather than assuming constant DFFM . Conclusions: The use of constant values for fat-free mass properties may increase bias when assessing body composition (FM and FFM) in children with obesity by two-component techniques such as ADP. Using adjusted corrections as proposed in the present work may reduce the bias by half.